Information System Audit on Employee Claim Application System Using COBIT 5 Framework - Syaifur Rahmatullah Abdul Rojak; Irmawati (Yayasan Kita Menulis, 2025)
PT ABC President Indonesia is a manufacturing company engaged in consumer goods, producing instant noodle and beverages packaged in ready-to-drink bottles with green tea and milk tea as the main ingredients. Sales promotions tailored to customer needs are expected to help achieve the company's goal of obtaining the best profits. Sales promotions such as giving rewards or discounts to customers with applicable terms and conditions. In the business process, the company has implemented information systems, one of which is the employee claim application menu advance, a system used for submitting payment claims for reward purchases. In implementation, advance submission from the user department is connected to the accounting and treasury departments. However, there are still shortcomings in the submission input process because supporting documents are still sent manually outside the system. There are no definite provisions regarding the completeness of the required documents to expedite the advance submission process, and there is no report menu that can be generated from the system. Based on this, an information system audit of the employee claim application system is needed using the COBIT 5 framework as the compatible method. Based on the results of the research, the current capability process values are as follows: DSS01 at 3.53, which is at level 4; DSS02 at 3.58, which is at level 4; MEA01 at 3.76, which is at level 4; and MEA02 at 3.40, which is at level 3. Therefore, the researcher provides recommendations for the selected processes so that the vision, mission, and objectives can be achieved according to the expected capability levels.